Numerical simulation of two-phase slug flow with liquid carryover in different diameter ratio T-junction - Pao, W. (Institute of Physics Publishing, 2017)
A smaller diameter conduit pointing at 12 o'clock position is typically hot-tapped to a horizontal laying production header in offshore platform to tap produced gas for downstream process train. This geometric feature is commonly known as T-junction. The nature of multiphase fluid splitting at the T-junction is a major operational challenge due to unpredictable production environment. Often, excessive liquid carryover occurs in the T-junction, leading to complete platform trip and halt production. This is because the downstream process train is not designed to handle excessive liquid. The objective of this research is to quantify the effect of different diameter ratio on phase separation efficiency in T-junction. The liquid carryover is modelled as two-phase air-water flow using Eulerian Mixture Model coupled with Volume of Fluid Method to mimic the slug flow in the main pipe. The focus in this paper is 0.0254 m (1 inch) diameter horizontal main arm and vertical branch arm with diameter ratio of 1.0, 0.5 and 0.3. The present research narrowed the investigation to only slug flow regime using Baker's map as reference. The investigation found that, contrary to common believe, smaller diameter ratio T-junction perform worse than larger diameter ratio T-junction. © 2017 Published under licence by IOP Publishing Ltd.